Komodifikasi Al-Qur’an: Analisis Filosofis Posisi Teks Suci dalam Kepentingan Komersial dan Politik Identitas: Analisis Politis Posisi Teks Suci dalam Kepentingan Komersial dan Identitas Kelompok - Fuad Ashari (SUARGA: Studi Keberagamaan dan Keberagaman, 2025)
This article aims to explore and analyze the phenomenon of Qur'anic commodification, which is the practice of converting Qur'anic texts into commodities traded for commercial gain and to serve identity politics. This research employs qualitative methods, including a literature study with a philosophical analysis approach, to explore the ethical and social implications of this practice. In a philosophical analysis, this article outlines how the practice of commodifying the Qur'an positions the text as a noble one used to attract customers and strengthen political identity. This study identifies two key dimensions: First, in the commercial realm, the practice of commodifying the Qur'an tends to overlook the sacred values and holiness inherent in the text. This research reveals how the marketing of products based on the Qur'an frequently overlooks ethical considerations and religious values in pursuit of maximizing profits. This raises questions about whether this practice conforms to the principles of fair business ethics and social responsibility. Second, in the context of identity politics, the commodification of the Qur'an can be used to reinforce the political identity of a particular group. The practice could spark debate about how religion is used as a tool to achieve political ends and influence relations between citizens and religions. In philosophical analysis, this article explores the conflict between the freedom of business and the protection of religious values within the context of identity politics. These findings underscore the importance of ethical reflection and philosophical understanding in grasping the implications of the commodification of the Qur'an. The article also emphasizes the importance of dialogue and thoughtful consideration among commercial, religious, and political values to achieve a balance that aligns with ethical principles and societal values.